The Influences of Service Quality and Satisfaction on Loyalty Intention: A Study of An Online Bookstore in Malaysia - Mirzaei, Soodeh (2010)
This study was aimed at confirming the dimensionality, relevance and quality of an online shopping service in Malaysia. Moreover, perceptions of service quality dimensions were assessed along with customer satisfaction.